(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
Taking as starting point two, seemingly opposite, recent decisions of the ECtHR and of the Italian Corte di Cassazione, in cases of international surrogacy, the paper analyses the difference between what can be considered as a proper surrogacy contract and what is nothing more than child-selling. In the first hypothesis, even if surrogacy contracts are prohibited and void in the most part of Europe, the genetic parental relationship between the child and at least one of the commissioning parents has to be recognized; in the other one, there is no parenthood at all, but the child will have the right to preserve a degree of contact with the persons however involved in his/her familial life.